2005
DOI: 10.1080/01676830590894671
|View full text |Cite
|
Sign up to set email alerts
|

Enucleation with Reverse Replacement of Sclera as an Alternative to Conventional Evisceration

Abstract: Combined enucleation and evisceration allows the selection and placement of an appropriately large-sized implant to achieve good volume replacement with no extrusions in our series. This technique is particularly pertinent as an alternative to standard evisceration in phtihisical eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…2000; Massry & Holds 2001; Choung et al. 2005; Madill & Maclean 2005; Sales‐Sanz & Sanz‐Lopez 2007). Fibrovascular ingrowth in the implant begins at the sclerotomy sites (Shields et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000; Massry & Holds 2001; Choung et al. 2005; Madill & Maclean 2005; Sales‐Sanz & Sanz‐Lopez 2007). Fibrovascular ingrowth in the implant begins at the sclerotomy sites (Shields et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this surgery, it is important to reduce volume loss and, at the same time, decrease tension on the surgical wound. Many techniques have been recommended to achieve these goals: relaxing scleral incisions, posterior sclerotomies, scleral flaps, implant coverage by multiple scleral layers and others (Stephenson 1987;Kostick & Linberg 1995;Lee et al 1995;Yang et al 1997;Long et al 2000;Massry & Holds 2001;Choung et al 2005;Madill & Maclean 2005;Sales-Sanz & Sanz-Lopez 2007). Fibrovascular ingrowth in the implant begins at the sclerotomy sites (Shields et al 1991;Sarvananthan et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It may also be possible to use autogenous sclera as durable material in cases with a high risk of severe inflammatory response, such as in children or patients with a history of recent trauma. The risk of sympathetic ophthalmia associated with evisceration could be reduced by this technique, although it is still unproven and the risk of sympathizing is exceedingly small following evisceration [28, 29]. Recently, a similar wrapping technique for enucleation using eviscerated autogenous sclera was reported as a small case series of 10 eyes [29].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of sympathetic ophthalmia associated with evisceration could be reduced by this technique, although it is still unproven and the risk of sympathizing is exceedingly small following evisceration [28, 29]. Recently, a similar wrapping technique for enucleation using eviscerated autogenous sclera was reported as a small case series of 10 eyes [29]. In this report, no complications were encountered, in particular no implant extrusions, and an appropriately large-sized implant could be placed to achieve a good volume replacement.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recent studies using posterior sclerotomy or scleral quadrisection report lower implant extrusion rates. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Other factors such as implant size, duration of antibiotic therapy and postoperative wound care regimen may play a role in implant extrusion. 32 Zolli reported 6% (3 of 48) extrusion with alloplastic implants 40 while Nunery et al reported less than 2% extrusion with alloplastic implants.…”
mentioning
confidence: 99%